Co‐expression of the calcitonin receptor gene in the hypothalamic kisspeptin neurons in female rats. (11th March 2018) - Assadullah,; Ieda, Nahoko; Kawai, Narumi; Ishii, Hirotaka; Ihara, Kunio; Inoue, Naoko; Uenoyama, Yoshihisa; Tsukamura, Hiroko
Abstract: Purpose: Hypothalamic kisspeptin neurons are considered to play a critical role in regulating mammalian reproduction and integrating humoral and neuronal inputs that control gonadotropin‐releasing hormone (GnRH)/gonadotropin release. The present study aimed to investigate the upstream regulator candidates for kisspeptin neurons. Methods: Visualized kisspeptin neurons that were taken from the arcuate nucleus (ARC) of Kiss1 ‐tdTomato rats were subjected to next‐generation sequencing (NGS) analysis. In situ hybridization (ISH) for the calcitonin receptor gene ( Calcr ) was performed throughout the whole forebrain of ovariectomized wild‐type female rats that had been implanted with a negative feedback level of estrogen, because the Calcr expression was evident in the ARC kisspeptin neurons from the NGS analysis. Then, a double ISH was performed for the Calcr and kisspeptin gene ( Kiss1 ) in the brain regions, containing either the anteroventral periventricular nucleus (AVPV) or ARC of the female rats. Results: The NGS analysis revealed that the Calcr was highly expressed in the ARC kisspeptin neurons. It was found that the Calcr was co‐expressed in 12% and 22% of the Kiss1 ‐expressing cells in the ARC and AVPV, respectively. Conclusion: The present study suggests that calcitonin receptor signaling could be involved in the regulation of reproductive function through the direct control of the ARC and/or AVPV kisspeptin neurons, and then GnRH/gonadotropin release.